COVID-related fibrosis: insights into potential drug targets. (2nd December 2021) - Sgalla, Giacomo; Comes, Alessia; Lerede, Marialessia; Richeldi, Luca
ABSTRACT: Introduction: Lung injury in severe COVID-19 pneumonia can rapidly evolve to established pulmonary fibrosis, with prognostic implications in the acute phase of the disease and long-lasting impact on the quality of life of COVID-19 survivors. This is an emerging medical need, and it has been hypothesized that antifibrotic treatments could have a role in ameliorating the fibrotic process in the lungs of these patients. Areas covered: The safety and efficacy of available antifibrotic drugs (nintedanib and pirfenidone) and novel promising agents are being assessed in several ongoing clinical trials that were performed either in critically ill patients admitted to intensive care, or in discharged patients presenting fibrotic sequalae from COVID-19. Literature search was performed using Medline and Clinicaltrials.org databases (2001–2021). Expert opinion: Despite the strong rationale support the use of antifibrotic therapies in COVID-related fibrosis, there are several uncertainties regarding the timing for their introduction and the real risks/benefits ratio of antifibrotic treatment in the acute and the chronic phases of the disease. The findings of ongoing clinical trials and the long-term observation of longitudinal cohorts will eventually clarify the best management approach for these patients.